Orphan’s judges in the captaincy of ceará: definitions of the idea of orphan and legal practices (1799-1822) - Assis, Patrícia Marciano de (Em Perspectiva, 2017)
This article aims to discuss the definitions of orphan from the documentation of Philippine’s Ordinations and practices of orphans’s Judges, situating the emergence of such judges in the Ceará’s Captaincy, in the colonial period, specifically between the years 1799-1822. Thus analyze inventories and “Registros da saída de dinheiro dos órfãos” of Arquivo Público do Ceará (APEC), the laws of Portugal, Philippine’s Ordinations, dictionaries, and other documents of Arquivo Histórico Ultramarino (HU), through theoretical and methodological contribution of History social. The proposal is to understand the power relations that circumscribe the ideas of "orphan" or "minor" in justice networks.